Politcs of History in the 21st Century: An Attempt How to Understand History or Necessity Dictated by the Reason of State - Polecki, Karol (Sensus Historiae, 2019)
The article is a reflection on the issue of understanding the past and possible ways to achieve it. The author considers the possibility of using projects described as historical politics, advocating the slogan of memory policy, to broaden the perspective of historical research. The elements influencing the interpretation frame work adopted by historians as well as the promoted postulate of adopting the attitude of an impartial observer in relation to the analyzed events are also described. The relation between history as a research discipline and memory is presented using the dialectical method. Starting from the opposition of these phenomena as mutually competing, the concept of cooperation is proposed.